The Determinants of Debt Financing - Zhao, Chenkai (2013)
Debt financing is an important part in capital structure. Over the fifty years, most scholars and researchers focus primarily on the balance between debt financing and equity financing. And only few research involve in types of debt financing, as well as the determinant of debt financing.